Effectiveness of breast crawl on the intensity of episiotomy pain and behavioral response among women during episiotomy suturing - Vevila Ronald Fernandes (Wolters Kluwer Medknow Publications, 2017)
Background: Methods to provide comfort and relieve pain are of paramount importance for the child bearing woman. Unfortunately very little importance is given to reduce the pain and discomfort of the women during episiotomy suturing. Aim: The aim of the study was to assess the effectiveness of breast crawl on the intensity of episiotomy pain and behavioural response among women during episiotomy suturing. Method: A quasi experimental design with a sample size (N=40) were selected using purposive sampling technique. The data were obtained by using a baseline proforma for the mother, Visual Analogue Scale (VAS) and an observation checklist. Statistical analysis was done using SSPS. Results: Findings showed that the present study findings also revealed that there is a significant difference in the mean scores of behavioural response of mothers during suturing between the experimental and control group (t38= 2.042, P < 0.05). Also there is a significant difference in the mean scores of reduction in intensity of episiotomy pain of mothers during suturing between the experimental and control group (t38=2.042, P < 0.05). Hence breast crawl is effective in reducing the intensity of pain during episiotomy suturing and there is a favourable behavioural response among women who received breast crawl during episiotomy suturing. Conclusion: The findings concluded that breast crawl is a simple and cost effective method to reduce the intensity of episiotomy pain in women during episiotomy suturing. Nurses can in co operate this practice and thus initiate the bond of motherhood.